Welfare, Income, and Budget Needs - David, Martin (The Review of Economics and Statistics, 1959)
R EAL disposable income is the measure generally accepted by economists as an indicator of the welfare of a household. Were we living in a world in which each individual formed a household and in which everyone required exactly the same goods to maintain himself, real disposable income might be an adequate measure. However, households are generally complex, and the income of a household must support a number of individuals whose daily requirements range from the nominal demands of a young child to the ample needs of an adolescent. Thus the welfare of a household must be measured not only by its income but also by the size of the household and the variety of needs of its members. This paper discusses a measure of welfare which relates the resources of a household to its needs. Estimates of welfare levels in the United States population based on this measure show that disposable income and per capita disposable income are extremely crude measures of welfare. Both overstate or understate the standard of living of an appreciable fraction of the United States population. The paper concludes with a few notes on the need for more accurate measures of welfare.